Tolerance Level of Butterfly Pea (Clitoria ternatea L.) to Stress Acidity Through Tissue Culture Technique - Kennaya Putri Aura Jannah; Panca Dewi Manu Hara Karti; Iwan Prihantoro (Buletin Peternakan, 2023)
Butterfly pea (Clitoria ternatea L.) a high-quality legume that is rich in protein and grows on various soil types with a pH range of 5.5-8.9. This experiment was conducted to get the level of tolerance of butterfly pea plants to stress acidity at different levels through tissue culture technique. The study was designed using a complete randomized design with 6 treatments with the different levels of AlCl3 addition using Murashige Skoog (MS) media with 20 replications (P0 (0 ppm AlCl3), P1 (100 ppm AlCl3), P2 (200 ppm AlCl3), P3 (300 ppm AlCl3), P4 (400 ppm AlCl3), and P5 (500 ppm AlCl3)). Data were analyzed using analysis of variance (ANOVA), and if there was a significant difference, data were further analyzed using Duncan’s multiple range test. The variables observed were acidity media changes, plant height gain, number of leaves, number of branches, number of tillers, percentage of leaves withering, and leaf color. The results showed that the butterfly pea plant has mechanism of adaptation to acid stress on the parameters of plant height gain and number of leaves at the end of the observation. However, the level of plant tolerance on the parameters of the number of branches and the number of tillers was ≤ 300 ppm (pH 3.73).